Preparation and characterization of high-purity PZT powders and ceramics made by modified spray-drying techniques - Wandee Thamjaree (2018)
The preparation and characterization of high-purity PZT powders and ceramics made by modified spray-drying techniques, where the cost of starting materials is high, was reported. A low-purity-grade (<99%) and comparatively low priced Pb(NO3)2, ZrO(NO3)2.6H2O, and C12H28O4Ti in a molar ratio of 1: 0.52: 0.48. The final solution was dried in a spray drier at 130°C to obtain fine granules. The physical properties, dielectric properties, and piezoelectric properties of the sintered ceramics were studied and found to be equivalent to the corresponding values of the ceramics produced from high purity chemicals.